2022
DOI: 10.1186/s13054-022-04164-0
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal and intestinal concentrations of opportunistic pathogens are independently associated with death of SARS-CoV-2 critically ill adults

Abstract: Background The composition of the digestive microbiota may be associated with outcome and infections in patients admitted to the intensive care unit (ICU). The dominance by opportunistic pathogens (such as Enterococcus) has been associated with death. However, whether this association remains all throughout the hospitalization are lacking. Methods We performed a single-center observational prospective cohort study in critically ill patients admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
4
1
Order By: Relevance
“…Our study expands the current literature by reporting a potential link between ICU-related microbiota alterations and 60 days mortality, in line with a recent study showing an association between day-90 mortality and higher concentrations of opportunistic pathogens in the oropharyngeal and intestinal compartments of critically ill patients [ 13 ]. Of note, our data should be interpreted with caution, as our sample size was not powered for multivariate adjustment.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Our study expands the current literature by reporting a potential link between ICU-related microbiota alterations and 60 days mortality, in line with a recent study showing an association between day-90 mortality and higher concentrations of opportunistic pathogens in the oropharyngeal and intestinal compartments of critically ill patients [ 13 ]. Of note, our data should be interpreted with caution, as our sample size was not powered for multivariate adjustment.…”
Section: Resultssupporting
confidence: 89%
“…12 Department of Internal Medicine, Baerum Hospital, Vestre Viken Hospital Trust, 1346 Gjettum, Norway. 13 Department of Anesthesiology and Intensive Care, Hammerfest County Hospital, Hammerfest, Norway. 14 Section of Gastroenterology, Department of Transplantation Medicine, Oslo University Hospital, Oslo,…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…A flourishing Enterococcus population often implies the fragile condition of the gut microbiota. Previous studies demonstrated that the elevated abundance of Enterococcus on admission was predictive of death or infection among ICU patients and was predictive of death from severe SARS-CoV-2 infection [ 33 35 ]. Moreover, our results demonstrate that Enterococcus exhibits a potent inhibitory association with most microbes and altered metabolites in sepsis patients.…”
Section: Discussionmentioning
confidence: 99%
“…They also constitute the second most commonly reported cause of surgical wound infections and the third most often reported cause of bacteremia [33,34]. Moreover, enterococci have been reported as the main Gram-positive bacteria causing hospital-acquired infections during and after the COVID 19 pandemic [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%